The Influence of Thermal History and Air Conditioner Use Behavior Under Different Cooling Set Point Temperature Modes on Health - Fangning Shi; Nianping Li; Haiyan Yan (Buildings)
Chinese local governments mandate public buildings to maintain a cooling set point temperature (SPT ≥ 26 °C). To explore how thermal history and air conditioner use behavior under different cooling SPT modes influence health, an experimental study and field investigation was carried out in split air-conditioned office buildings in China’s cold climate regions. Two categories were established based on energy policy: the H group (SPT ≥ 26 °C) and the L group (SPT < 26 °C). The results showed that L group subjects experienced longer, colder, and higher CO2/formaldehyde exceedance rate exposures in air-conditioned environments, demonstrating greater reliance on air conditioners, although indoor air quality satisfaction showed no significant difference between groups. Air quality perception demonstrates long-term adaptation to indoor air temperature and CO2. Compared with the high SPT mode, the adverse influences and mechanisms of the low SPT mode on health are as follows: making people adapt to cold environments due to colder thermal history and inducing pathological adaptation cycles, thus promoting strong reliance on the air-conditioned environment. This leads to a substantial increase in air conditioner use time, thereby increasing the severity of sick building syndrome (SBS), indoor pollutants, formaldehyde carcinogenic risk, and desensitized air quality perception. China’s government should systematically enhance the enforcement of SPT-related policies.